The foundations of the conflit de langage over land and forest in southern Cameroon - Oyono, P.R. (2005)
When Germans colonized Cameroon in the nineteenth century, most of the ethnic groups living in the forest zone had already established territories. However, Germany then became the legal owner of land and forests. This brutal cohabitation of the new version of the state and customary systems of territorial management generated serious problems and has continued to this day in post-independence Cameroon. Among these problems, this paper focuses on the conflit de langage (conflict of language or of discourse) between the state and local communities on land and forests ownership and on the regulation of access to natural resources. This article reconstructs the foundations of this conflit de langage, by revealing elements such as the exclusion of indigenous systems and the requirements of capitalist accumulation. The author explores various property rights formation processes and forestry legislations (German, British, French and post-independence). The article points out how the situation has worsened through the creation of forest concessions on customary lands, the creation of protected areas, the sharing of revenues from commercial logging, the establishment of agroindustries, and oil compensation.